2012
DOI: 10.1002/ejoc.201200685
|View full text |Cite
|
Sign up to set email alerts
|

A Stereoselective Route to Aza‐C‐aryl Glycosides from Arynes and Chiral Nitrones

Abstract: Arynes are regarded as potential and versatile intermediates in organic synthesis. These highly‐reactive, strained and kinetically unstable species have numerous applications in synthetic chemistry. In this article, a highly‐diasteroselective and efficient 1,3‐dipolar cycloaddition reaction between a range of arynes and sugar‐derived cyclic nitrones leading to an interesting class of sugar‐based benzo[d]isoxazolines is described. These benzo[d]isoxazolines upon selective N–O bond cleavage provide various subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…7,8 Following the seminal work of Kaliappan's goup, 4 we studied the cycloaddition of dialkoxypyrroline N-oxides with benzyne as another entry to radicamine or codonopsinine analogues. In particular, the lack of substitution on C-5 of the nitrone could allow the introduction of various substituents by following the well-known alkylation of the nitrone following the oxidative opening of the hexahydropyrrolo[1,2-b]isoxazolidine ring.…”
Section: Scheme 1 Retrosynthetic Analysis Of 2-aryl-polyhydroxy-pyrromentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Following the seminal work of Kaliappan's goup, 4 we studied the cycloaddition of dialkoxypyrroline N-oxides with benzyne as another entry to radicamine or codonopsinine analogues. In particular, the lack of substitution on C-5 of the nitrone could allow the introduction of various substituents by following the well-known alkylation of the nitrone following the oxidative opening of the hexahydropyrrolo[1,2-b]isoxazolidine ring.…”
Section: Scheme 1 Retrosynthetic Analysis Of 2-aryl-polyhydroxy-pyrromentioning
confidence: 99%
“…In Kaliappan's work 4 there is no mention of such a rearrangement product. However, the absence of the side product in those reactions can be explained by the lower nucleophilicity of the isoxazolidine nitrogen in B (R′ = Bn; R = CH 2 OBn, Scheme 1), which is shielded by a bulky adjacent benzyloxymethylene group.…”
Section: Letter Syn Openmentioning
confidence: 99%
See 1 more Smart Citation
“…SCHEME 14 1,3-dipolar cycloaddition of α,β-unsaturated nitrones with arynes [37]. Very recently Khangarot and Kaliappan reported a 1,3-dipolar cycloaddition reaction of sugar-derived chiral nitrones 28 with arynes to synthesize the sugar-based benzo [d] isoxazolines with high-diasteroselectivity (Scheme 16) [39]. Recently, Larock and coworkers reported an efficient synthesis of benzisoxazolines by the 1,3-dipolar cycloaddition of nitrones with arynes generated from the Kobayashi precursor 1 using CsF in THF (Scheme 15) [38].…”
Section: Synthesis Of Benzisoxazolinesmentioning
confidence: 99%
“…Nitrile oxides can be generated by the dehydrohalogenation of chlorooximes 31 under basic conditions. SCHEME 16 Synthesis of aza-C-aryl glycosides [39]. The research groups of Moses [40], Larock [41], and Browne [42] independently reported the efficient 1,3-dipolar cycloaddition reaction of in situ-generated nitrile oxides with arynes leading to the synthesis of benzisoxazoles.…”
Section: Synthesis Of Benzisoxazolesmentioning
confidence: 99%